The parents behavior in the sports - Santiago Romero Granados; María Encarnación Garrido Guzmán; María Luisa Zagalaz Sánchez (FEADEF, 2009)
This article comes from the interest in learning about the behaviour of parents in the sport of her child in the Municipal Sports Academies in Sevilla. The aim of the study is to know how much parents are able to get involved in sport practiced by their children, which behaviours they adopt and which points of view have sport technicians and children themselves of that involvement, analyzing whether all this is done as educational or not. The study consists of a sample of parents, children and technicians from different Municipal Sports Academies in Sevilla, to which were passed out a questionnaire related to the behaviour and attitudes of parents in their children's sports, both at the level of training and level of competitions in which their children are involved. The results show that participation is largely dependent on the practiced sport and on the districts where the children involved. There are differences regarding the behaviour of both parents in training, competition, involvement ... according to where they belong.